Assessing thermophysical properties of Nanostructured Cellulose Nano Crystal (CNC) and Graphene Nanoplatelets (GNP) Additives in Palm Oil-Based Heat Transfer Fluid - Kulandaivel, Sridhar; Samykano, Mahendran; Ngui, Wai Keng; Suraparaju, Subbarama Kousik; Reji Kumar, R. (EDP Sciences, 2024)
This study explores the examination of the thermophysical characteristics of eco-friendly CNC-Palm oil, GNP-Palm oil and CNC/GNP-palm oil mono and hybrid nanofluids. The stability assessment involves a comprehensive analysis, incorporating visual observations and thermal conductivity assessments. Notably, it was observed that an elevated proportion of hybrid mixture contributed to the enhanced stability of the nanosuspension, ensuring the uniform dispersion of nanomaterials within the base liquid for an extended period. The results indicate that hybrid nanofluids containing CNC/GNP and formulated with palm oil exhibit substantial stability. A comprehensive visual examination over an impressive 30-day duration reveals minimal accumulation, underscoring the enduring stability of these nanofluids. The study also examines crucial thermal and physical properties, including thermal conductivity and viscosity about temperature. The most significant enhancement was witnessed in thermal conductivity, achieving a noteworthy 100% increase in the 0.1w/v% concentrated CNC/GNP/Palm Oil hybrid nanofluid at 70°C, demonstrating a significant improvement compared to the base fluid. Furthermore, there are noticeable increments in viscosity, albeit with a more modest enhancement compared to thermal conductivity. These outcomes suggest a direct relationship between the increased concentrations can improve stability and thermal conductivity. This study contributes valuable insights into utilizing CNC/GNP in nanofluid applications, with implications for fields requiring enhanced thermal performance and fluid stability.